2003
DOI: 10.1007/s005950300024
|View full text |Cite
|
Sign up to set email alerts
|

Stanford Type A Aortic Dissection which Ruptured into the Left Atrium: Report of a Case

Abstract: A Stanford type A aortic dissection ruptures usually into the pericardial space or the mediastinal space. We herein report the rare surgical case of a Stanford type A aortic dissection which ruptured into the left atrium. The patient had a previous history of mitral valve replacement. The time and the cause of the aortic dissection was unclear. At operation, adhesions around the proximal aorta and between the aortic root and the left atrial roof were confirmed to be one of the causes for this rare form. A fist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Aorto‐left atrial fistulae have been reported in a number of different clinical settings, including infective endocarditis of the aortic valve, 1 Stanford type A aortic dissection, 2 following Amplatzer device closure of an atrial septal defect 3 and aortic valve replacement 4 . These communications have variable clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…Aorto‐left atrial fistulae have been reported in a number of different clinical settings, including infective endocarditis of the aortic valve, 1 Stanford type A aortic dissection, 2 following Amplatzer device closure of an atrial septal defect 3 and aortic valve replacement 4 . These communications have variable clinical implications.…”
Section: Introductionmentioning
confidence: 99%